Uma porta fechada ao devaneio: uma aplicação a textos sânscritos dos esquemas de abordagem linguístico-retórica de Isaac Nicolau Salum - Fonseca, Carlos Alberto da (Classica - Revista Brasileira de Estudos Clássicos, 1989)
In four articles issued between 1971 and 1975, Isaac Nicolau Salum outlined the main ideas of a “linguistic-rhetorical approach” method to texts not giving it a definitive form, which was, however, tried to be attained by means of inumerable text schematization exercises published in eleven booklets up to 1979.Rescuing some of lhe scattered proposals in those writings, this article aims at meditating about the method value for a critical study of texts and for the analysis of the speech, and at the same time, as a corroboration of the procedure effectiveness. applying it to the characterization of Nala and Damayanti, characters of a parallel account to the narrative structure of the Sanskrit epic poem Mahābhārata, for whom it reveals rhetorical dimensions that a less attentive reading will neglect.